Multinational enterprises' foreign direct investment location decisions within the global factory - Bartels, Frank L. (UNIDO ViennaAT, 2009)
Explains the concept of the global factory. Examines the meaning of globalisation and shows that the varied pace of globalisation across a range of markets provides the context for the emergence and dominance of the global factory. Examines the difficulties of the least developed countries (LDCs) in participating in the spread of global factories. Analyses the severe obstacles confronting emerging countries in building global networks and in extending their participation beyond the role of contract manufacturing. Examines the ability of the currently dominant global factories (largely from developed countries) to maintain thier global competitiveness.